Comparative Study on the Cracking Sounds During Two Rotary Manipulations of Neck - 李义凯 赵卫东 钟世镇 (Journal of acupuncture and tuina science, 2006)
Objective: To improve the accuracy of the rotary manipulations of the neck in the treatment of neck pain, according to subjective and objective clinical findings.Methods: Two groups of 60 outpatients diagnosed with neck pain were suited to the manipulation and each group was 30 cases. The diagnosis of neck pain was made with conventional clinical evaluation, including history, palpation examinations, CT scan and X-ray. Group A received a manipulation of obliquely pulling the neck. While group B received manipulation of pulling the rotated and located neck. Subjects received a maximum of 10 treatments over a 3-week treatment period. Both treatment groups were assessed with subjective (cervicodynia, neck discomfort, upper limb numbness, vertigo and tinnitus) and objective (cracking sounds). The cracking sounds during two of the manipulations were recorded by a microphone positioned at both sides of the neck. The sounds were compared in patients of two groups. Statistical analysis was conducted with a one-factor within-subjects analysis of variance tests and descriptive statistic.Results: Analysis of the subjective indicated that the cases with upper limb numbness were reduced from 12 to 6 in group 2, while the cases with vertigo and tinnitus were reduced from 13 to 4 in group 1. Analysis of the objective indicated two kinds of neck rotary manipulations act not only on the rotary-side facet joints, but on the opposite to the rotary side only in a few cases. The results showed that manipulation of pulling the rotated and located neck has a small action range and centralized action points, while manipulation of obliquely pulling the neck has many action segments and discentralized action points.Conclusion: It was concluded that the rotary manipulations act mainly on the rotary side, not on the opposite, and that manipulation of obliquely pulling the neck has a wider action range and a better therapeutic effect on cervical upper-segment lesions, while manipulation of pulling the rotated and located neck has a limited action range and is suitable for cervical lower-segment lesions. There were some relations between the joint sounds during the manipulation and clinical curative effect.